P112 Therapeutic Whole Lung Lavage For Silicosis – First Application in the UK. (19th November 2012) - Prudon, B; Attanoos, R; Morgan, C; Stenton, SC
Abstract : Silica is a highly fibrogenic dust and this is reflected in the low amounts of dust found in the lungs of those with fatal silicosis – approximately 3g in total. Despite a low workplace exposure limit for respirable silica, new cases of silicosis continue to be diagnosed. There is no effective pharmacological treatment. In China, whole lung lavage (WLL) has been performed for silicosis with evidence of improved dyspnoea at 6 months. To our knowledge the technique has not previously been attempted in the UK. We carried out WLL in 2 stonemasons with silicosis. Patient A presented aged 41 in 2007 with MRCP dyspnoea score 3, FVC 3.27L (60% predicted), and radiographic features of extensive silicosis (Category 3R, ILO classification). To determine if mineral could be removed from his lungs, a bronchoscopic lavage was performed using 180ml saline. The lavage fluid contained 4.8g/l of mineral. WLL was then performed with 7L saline on the right, and a month later 12L on the left. Each procedure lasted approximately 1 hour and the patient was discharged without complication within 24 hours. The washings contained 0.66g/l mineral. The total removed was approximately 7.9g, 50% of which was silica, (silica content was determined by transmission electron microscopy with energy dispersive x-ray spectrometry). On review at 6 months there had been no clinical or radiological changes. Patient: B presented aged 31 with MRCP dyspnoea score 2, FVC 3.96L (65% predicted), and radiographic features of silicosis (Category C). A 9L right WLL produced considerably less mineral (0.09g/l: total approximately 0.1gm). 21% was silica. These cases demonstrate that WLL is acceptable and safe in patients with silicosis in the UK, and that substantial quantities of mineral can be removed from the lungs. It is postulated that reducing the silica burden will slow the rate of disease progression, but there is no evidence in support of that. Evidence will be difficult to adduce given the variable nature of silicosis and its relatively slow rate of progression. In the meantime, we suggest that WLL is considered for younger patients with advanced silicosis.